Comparing performance during evening and night session among men hockey players at Sekolah Menengah Sains Tuanku Munawir / Hamidah Yazid - Yazid, Hamidah (2018)
Time of a day is a main factor that influences the opt1m1zation of athlete performance. The objective of this study is to identify training time that will be more effective in enhancing athlete performance. A comparative study involving 12 participants (n=12) was carried out. The participant was selected using purposive sampling technique. The subject ages 15 years old and men hockey players. The subject underwent three physical fitness tests in two sessions; first session was held in evening (4.00p.m.) and second session held in the night (8.00p.m.). The test is vertical jump test (Power), Illinois agility test (Agility) and bleep test (VO2max). The duration of data collection was two weeks. All subject underwent familiarization. Start with vertical jump test there are given, Illinois agility test and bleep test. The rest period between test are 3 minutes to 5 minutes. The finding of this study indicates that there was a significant different between comparing the effect of evening training on agility among men hockey players. However, there are no significant difference between comparing the effect of evening training and night training on cardio endurance and power among men hockey players at SM. Sains Tuanku Munawir. In conclusion, agility performance showed pattern of improvement in evening training.